PKM Penerapan Sistem Informasi Desa Untuk Meningkatkan Pelayanan Berbasis Digital - Andi Akram Nur Risal; Alifya Nurilmi Fony Hasanuddin; Fathahillah; Suhardi, Iwan; Syahrul (Jurusan Teknik Informatika dan Komputer, 2023)
The Village Information System is an innovative solution to optimize village data management and speed up access to information for the community. The development of Information Technology has become an urgent need in order to improve the efficiency and quality of services at the village level. This research aims to implement a Village Information System to improve digital-based services in the village environment. The implementation of the Village Information System is expected to increase the efficiency of data management and speed up the decision-making process at the village level. The application of digital-based technology is expected to provide easier and faster access for the community to obtain information and services from the village government. Services such as population administration, licensing and development monitoring can be accessed online, minimizing the time and costs required. Apart from that, the Village Information System also provides opportunities for active community participation in decision making through feedback features and discussion forums. This research strengthens the concept of clean and transparent government, because the Village Information System creates openness to public information. This research makes a positive contribution in exploring the potential of information technology to optimize village governance and improve the quality of life of the community as a whole. This is the reason researchers consider it important to develop and implement a Village Information System to improve digital-based community services.